(untitled) (São Paulo Journal of Mathematical Sciences, 2009)
In this work, we describe a method to construct central polynomials for F-algebras where F is a field of characteristic zero. The main application deals with the T-prime algebras Mn(E), where E is the infinite- dimensional Grassmann algebra over F, which play a fundamental role in the theory of PI-algebras. The method is based on the explicit decomposition of the group algebra FSn. AMS Classification 2000: Primary 16R10, Secondary 16W50, 15A75. Keywords: Polynomial identities, central polynomials, Grassmann algebra.